Comportamiento de la especie cumala preservada (Virola sp) al secado natural en las instalaciones de la planta de transformación primaria Maderas Acasia SAC - Arbildo Arevalo, Jorge (2017)
This research work was carried out in the facilities of MADERAS ACASIA SAC primary transformation plant owened by Mr. Elias Cruzado, which is located in the town of San Jóse de Cochiquinas, in Pevas district, Mariscal Ramón Castilla province, Loreto department; with the purpose of determining the behavior of the preserved cumala (virola sp.) to natural drying on the trestle. The results show us that the initial moisture content is 102%, an average final moisture contento f 17% reaching an equilibrium moisture content after air drying stacked on a trestle is 17% in 70 days of drying. The highest percentage od defects is due to cracks, which amounts to 2.07%, followed by cracks 1.49%, twists 1.22%, bends 0.96% and other defects 0.62%, with the yield of the Cumala sawn Wood after drying in the open air was 96.64% and defective Wood was 6.36%. According to these results, the preserved cumala sawn wood can be classified according to a type of FAST DRYING by the method of stacking on a trestle.